Case study: installation of canal control structures on the Government Highline Canal - Khalsa, Ram Dhan, author; Styles, Stuart, author; Burt, Charles, author; Norman, Bob, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2002)
The Government Highline Canal Modernization Study was completed in April 2000 to evaluate options for reducing the flow rate requirement of the Government Highline Canal in order to increase the water supply in the "15-Mile Reach" of the Colorado River, thereby helping sustain habitat for fish species identified as endangered. The intent was to develop a design for which Colorado River diversions could be better matched to on-farm demands. It was determined that canal modernization, in the form of automated canal structures, in-system storage, and new operational procedures could significantly reduce operational spill. A systematic evaluation of the existing canal system and operations identified a potential savings of 28,500 acre-feet of water that could remain in the river or be returned to the river upstream of the 15-Mile Reach. This paper is an update to one done in 1999 for USCID about the Modernization Study. This paper will focus on the lessons learned from the actual implementation of the recommended structural and operational improvements, in particular the construction of the main components of this project including canal control structures.
USCID/EWRI conference
Government Highline Canal
Not digitized by CSUL Digital Services.
Presented at the 2002 USCID/EWRI conference, Energy, climate, environment and water - issues and opportunities for irrigation and drainage on July 9-12 in San Luis Obispo, California.